Thickening of municipal sludge using recycled coagulant - Hamid, A.H.A.; Isa, M.H.; Kutty, S.R.M. (2008)
This study investigated the effectiveness of a coagulant, recycled ferric chloride (RFC) as a coagulant for reused in thickening of municipal sludge. RFC is generated from sludge produced from a groundwater treatment plant through a digestion process. In the experimental study, jar tests were conducted on sludge obtained from a wastewater treatment plant. In the jar tests, coagulants such as alum, ferric chloride, ferric sulphate and RFC were evaluated. Settleability tests were conducted in the thickening process. The supernatant were then measured for chemical oxygen demand (COD), colour, and total suspended solids (TSS). Tests were conducted in triplicates. The raw sludge settling rate was found to be 2.4 cm/min. The optimum settling rates for alum, ferric chloride, ferrous sulphate and RFC was found to be 3.13 cm/min, 1.86 cm/min, 2.5 cm/min and 4.5 cm/min. RFC improved the settling rate by 88% and also removed colour, COD and TSS at 42%, 54% and 88%, respectively at the optimum settleability dosage.